Associação entre o líquen plano bucal e a hepatite crônica pelo vírus C - Soraya de Mattos Camargo Grossmann (2005)
It was aimed at, with the present work, to investigate the possible association between the buccal plane lichen and the chronic hepatitis for the virus C. With the approval of the Committee of Ethics of UFMG, and after signature of the Term of free and illustrious Consent, they were appraised 50 patient with buccal LP (GROUP 1) of University of Dentistry of UFMG, and 215 patient with chronic hepatitis for the virus C (GROUP 2) of the Clinic of Hepatitis you Turn of the Instituto Alfa of Gastroenterologia of the Hospital of the Clinics of UFMG. The patients of the GROUP 1 underwent exams sorológicos anti-HCV for infection investigation for the virus of the hepatitis C, and the patients of the GROUP 2 were appraised intrabucalmente, with relationship to the presence or not of lesions of LP. The exam sorológico followed protocol of the Central Laboratory of the Hospital of the Clinics of UFMG, and the exams clinical intrabucais followed a standardized sequence, being observed the universal norms of biossegurança. The collected data were analyzed by the exact test of Fisher, being considered the level of significância of 5%. A case of hepatitis C chronicle was diagnosed in the GROUP 1 (2,00%), not being significant estatisticamente (p = 0,464). In the GROUP 2 buccal LP was diagnosed in five patient (2,33%), with statistical significância (p = 0,002). Our results suggest that buccal LP can be considered an extra-hepatic manifestation of the chronic hepatitis by the virus C, although the association among those two entities should be investigated better.